IMPROVEMENT OF ENTERPRISE MANAGEMENT SYSTEM - Mamatov Mirziyod (Scholar Express Journals, 2024)
The objective of the article is to highlight and consider the main directions for improving the modern enterprise management system, since that in the modern market conditions, the issue of effective development for industrial enterprises becomes more relevant, while the fundamental bearing core of the enterprise's internal environment is the management efficiency. The main problem is the managerial inefficiency of an excessively large structure that is not well suited to the work in market conditions. In the course of this analysis, the management system of an industrial enterprise was considered as a complex open system with the use of the system analysis methodology in the study, which made it possible to identify the main directions for its improvement.
Keywords: enterprise; controlling; business processes